Accelerating the Development of Bangka Island through Sustainable Tourism by Strengthening the Roles of Multi-stakeholder - Firdaus, Nur; Endah, Nur Hadiati (UI Scholars Hub, 2016)
Bangka-Belitung Islands Province, located in the Karimata Strait, offers a number of benefits that can be optimized to promote the development in the region through the development of the tourism sector of the province. The magnificence of its natural scenery, culture, and history are the main attractions for international tourists to pay visit to the region. However, the development of the tourism sector in the Province tends to be concentrated in Belitung Island while Bangka Island has not received serious attention from the local government. The purpose of this research paper is to identify and explore the option of sustainable tourism to promote the development of Bangka Island. The data of this study are collected from in-depth interviews, focus group discussion (FGD), and observations. In addition, secondary data is also for further analysis. The results of this study show that sustainable tourism is required to increase the regional development in Bangka Island. However, several problems, such as environmental issues in relation to the tin mining activity in the region as well as ineffective coordination among stakeholders hamper the development of tourism sector. The approach of sustainable tourism, which emphasizes the roles of stakeholders, will be able to serve as the locomotive to develop the tourism sector in the region and, subsequently, the future development of Bangka Island in general. The contribution of this study is to encourage the development of sustainable tourism with a comprehensive approach through strengthening the roles of stakeholders. Keywords: economic development, sustainable tourism, stakeholders, tourism